Natural ventilation around open ground floor or pilotis of high rise residential building: harmonization of modern with traditional housing in tropical areas - Sapian, Abdul Razak; Abdul Majid, Noor Hanita; Hokoi, Shuichi (2012)
In Malaysian villages, traditional Malay houses are the most common type of housing. One of the main features of these traditional houses, which are located in hot and humid areas of Malaysia, is an open ground floor created by using pilotis, which raises the first floor of the house, leaving the ground floor open (Fig. 1). Thus, a shaded free space with good air circulation is obtained, which can be used by residents and their neighbors for working and leisure activities. These traditional Malay houses are not suitable for cities because the availability of land in urban areas is limited. Although high-rise residential buildings accommodate a large number of residents in a limited area, and the airflow on the higher floors of these buildings is adequate, the fact that sufficient airflow cannot be expected near the ground floor must be taken into consideration.